Comparative analysis of availability of the medicines for privileged categories of citizens suffering from diabetes mellitus in the Russian federation and Ukraine based on the pharmaceutical law - Shapovalov, V (Jr); Shapovalova, V; Shapovalov , V; Rogozhnykova, O (Annals of Mechnikov's Institute, 2020)
World Health Organization paid close attention to the timely detection and treatment of diabetes mellitus, since there are more than 382 million people suffering from this disease in the world. Life expectancy of patients with diabetes mellitus is twice as less when compared to their peers who do not suffer health problems and leading a healthy way of life. Based on the statistical data shows that 80% of patients on diabetes live in countries with a low standard of living. The dynamics of diabetes considered not only as a serious disease, but also as an important medical and pharmaceutical, social, economic and criminal legal problem, which is now very important for the Russian Federation, Ukraine and other countries of the world. This is because there is a constant increase in the number of patients suffering from diabetes on, with chronic diseases, the development of micro- and macrovascular complications, which lead to a reduction in life expectancy due to deterioration of its quality. At the same time the availability of the medicines for privileged categories of citizens, who suffer from diabetes mellitus in the Russian Federation and Ukraine depends on many factors. Some of these factors are improving of the management measures and control over the circulation of medicines (drugs); prevention and disease prevention; the use of personalized pharmacotherapy; ensuring the availability of essential medicines for privileged categories of citizens.Therefore, the aim of the work was to study the particularities of legal documents in Ukraine and Russia, aimed at organizing the rules regulating the circulation of the medicines used for diabetes mellitus pharmacotherapy by generalizing forensic and pharmaceutical practices related to the violation of the rights of patients with diabetes. To improve the system of measures of state control over the increasing availability of medicines for citizens of privileged contingent based on the norms of pharmaceutical law. In the study researched the particularities of legal documents in the Ukraine and Russian Federation aimed at organizing rules regulating circulation of the drugs used in the pharmacotherapy of diabetes. Found that pharmaceutical law in the field of public administration in the Russian Federation and Ukraine is the foundation and guarantor in protecting the rights of states declared the privileged category of people suffering from diabetes mellitus on unrestricted access to essential drugs. Established that the Ministry of Healthcare of Ukraine and the Ministry of Healthcare of Russian Federation must provide scientific advice for the prevention of diabetes mellitus; update in accordance to the European standards and directives, standards of diagnosis, clinical protocols and rules of care for patients suffering from diabetes mellitus; raise public awareness about the global epidemic of diabetes; analyze forensic and pharmaceutical practice as a result of violations of the rights of patients with diabetes to ensure preferential (free) drugs. Ensuring the rights of patients with diabetes mellitus and providing vital medicines of all classification and legal groups, should base solely on the norms of medical and pharmaceutical law, the Constitution and laws of Ukraine. This will enable to the government to control the process of the licensing conditions for the implementation of activities related to the circulation of drugs among the healthcare facilities (pharmacies and hospitals).